The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.wneu.2019.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Surgery and Radiotherapy for Symptomatic Spinal Metastases in a Belgian Specialist Center

Abstract: Cost-utility analysis of surgery and radiotherapy for symptomatic spinal utility analysis of surgery and radiotherapy for symptomatic spinal utility analysis of surgery and radiotherapy for symptomatic spinal utility analysis of surgery and radiotherapy for symptomatic spinal metastases in a Belgian specialist center. metastases in a Belgian specialist center. metastases in a Belgian specialist center. metastases in a Belgian specialist center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
12
2
Order By: Relevance
“…While prior studies with a high proclivity for confounding by indication maintained an association between surgical intervention and survival, [13][14][15] such a link was not observed in our cohort. The overall mortality rate for our cohort at both 1-and 2 years is aligned with other work, such as that of Ghori et al, 10 Turner et al, 14 and the prospective series of Fehlings et al 20 In studies that have accounted for selection bias for surgery using causal inference techniques, or other statistical approaches, the survival benefit associated with surgery has been marginal at most and usually only realized over the course of the first 6 months following treatment.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…While prior studies with a high proclivity for confounding by indication maintained an association between surgical intervention and survival, [13][14][15] such a link was not observed in our cohort. The overall mortality rate for our cohort at both 1-and 2 years is aligned with other work, such as that of Ghori et al, 10 Turner et al, 14 and the prospective series of Fehlings et al 20 In studies that have accounted for selection bias for surgery using causal inference techniques, or other statistical approaches, the survival benefit associated with surgery has been marginal at most and usually only realized over the course of the first 6 months following treatment.…”
Section: Discussioncontrasting
confidence: 83%
“…5,11 Over the last 15 years, surgical treatment has been touted as a means to preserve functional independence, quality of life, and improve the prospect for survival. 4,5,[12][13][14][15] A balanced assessment of the literature supporting these notions, however, raises concern for both selection bias and confounding by indication. Nonrandomized clinical series were limited as only patients with favorable survival characteristics were eligible for surgery, while those who would not tolerate surgical intervention, or who were deemed poor candidates, received palliative nonoperative care.…”
mentioning
confidence: 99%
“…In Japan, Miyazaki et al [ 2 ] also found surgical treatment to be cost-effective with an ICER of 42,003 USD per QALY gained at a WTP of 50,000 USD per QALY gained. Finally–in Belgium, Depreitere et al [ 7 ]. Reported an ICER for surgical management of spinal metastasis of 13,635 EUR per QALY compared to radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…CUA studies that compared surgical treatment and radiotherapy alone for the treatment of spinal metastasis have been reported in Japan, the United Kingdom, Belgium, Canada, and the United States. The results of those studies showed combination surgery and radiotherapy to be cost-effective compared to radiotherapy alone for treating spinal metastasis in developed countries [ 2 , 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Cost involved in spine tumor metastatic surgery have been looked in few studies globally. [12][13][14][15] With prolonged life expectancy, the overall cost of cancer treatment incurred can be manifolds. Significant efforts are being made to make spine surgery cost effective without compromising outcomes.…”
Section: Introductionmentioning
confidence: 99%